The Effect of Physical Exercise on the Recurrence of Atrial Fibrillation: A Meta-Analysis - Prastika Dica Izwara; Muthia Tsabita Rahmi; Kesowo Soejoko; M. Dzikrul Haq Karimullah; Wirawan Prabowo (Yayasan Mata Pena Madani, 2026)
Evidence on the benefits of physical exercise on AF recurrence after therapy is still limited. This meta-analysis evaluated the effect of physical exercise programmes on AF recurrence. Studies followed the PRISMA 2020 guidelines and were registered in PROSPERO. Literature searches were conducted in PubMed, Scopus, and the Cochrane Library (2020–2025). RCTs in adult patients with post-treatment AF and exercise interventions ≥6 weeks were included. The primary outcome was AF recurrence, with secondary outcomes being VO₂max and quality of life. Analyses were performed using RevMan 5.4.1 with a random-effects model. Nine RCTs with a total of 760 participants were analysed. The duration of the intervention ranged from 12 weeks to 12 months. A meta-analysis of three studies (287 participants) showed a significant reduction in the risk of AF recurrence with a risk ratio of 0.77 [95% CI 0.66–0.89; p=0.0006; I²=0%]. VO₂max increased by 2.77 mL/kg/minute [95% CI 0.59–4.94; p=0.01; I²=36%]. Quality of life improved with a mean difference of 4.47 [95% CI 1.41–7.53; p=0.004; I²=82%]. Physical exercise programmes effectively reduce AF recurrence by 23%, improve cardiorespiratory capacity, and enhance patients' quality of life. Physical exercise should be integrated as a standard component in comprehensive AF management alongside risk factor control.